2023
DOI: 10.3390/healthcare11050766
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal and Skin Microbiome in Patients with Atopic Dermatitis and Their Influence on the Course of the Disease: A Literature Review

Abstract: Bacteria inhabiting the digestive tract are responsible for our health. The microbiome is essential for the development of the immune system and homeostasis of the body. Maintaining homeostasis is very important, but also extremely complicated. The gut microbiome is related to the skin microbiome. It can therefore be assumed that changes in the microbes inhabiting the skin are greatly influenced by the bacteria living in the intestines. Changes in the composition and function of microbes (dysbiosis in the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…All these actions are mediated through different mechanisms, including specific G protein coupled receptor family (GPCR) and epigenetic effects [78][79][80][81]. Disruptions in gut microbiome balance and the further, activation of T-cells via interactions with pa ern recognition receptors and Toll-like receptors triggers an inflammatory process and induces autoimmune conditions such as rheumatoid arthritis [82], inflammatory bowel disease [83], systemic lupus erythematosus [84], multiple sclerosis [85], psoriasis [56,[65][66][67][68][69][70][71][72], as well as other skin alterations, such as atopic dermatitis [86] and vitiligo [87].…”
Section: Microbiomementioning
confidence: 99%
“…All these actions are mediated through different mechanisms, including specific G protein coupled receptor family (GPCR) and epigenetic effects [78][79][80][81]. Disruptions in gut microbiome balance and the further, activation of T-cells via interactions with pa ern recognition receptors and Toll-like receptors triggers an inflammatory process and induces autoimmune conditions such as rheumatoid arthritis [82], inflammatory bowel disease [83], systemic lupus erythematosus [84], multiple sclerosis [85], psoriasis [56,[65][66][67][68][69][70][71][72], as well as other skin alterations, such as atopic dermatitis [86] and vitiligo [87].…”
Section: Microbiomementioning
confidence: 99%
“…Therefore, it is recommended to promote the development of the physiological intestinal flora from childhood through min. breastfeeding, the use of probiotics with the aim of preventing the development of atopy [ 67 , 68 , 69 ]. In AD patients, there is a significant depletion of the intestinal microbiota, ex.…”
Section: Gut Microbiota In Atopic Dermatitismentioning
confidence: 99%
“…In AD patients, there is a significant depletion of the intestinal microbiota, ex. Lactobacillus and Bifidobacterium , with a concomitant overrepresentation of Escherichia coli and Clostridium difficile and, importantly, as in the case of the skin microbiota, an abundant occurrence of S. aureus [ 68 , 69 , 70 ]. The mycobiota, the fungal part of the microbiota, is also altered in atopy: there is a reduced occurrence of Malassezia with Saccharomycetales , Rhodotorula , and Candida increase [ 71 , 72 , 73 ].…”
Section: Gut Microbiota In Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the microbiome is associated with susceptibility to a range of diseases such as cancer, diabetes, allergy, obesity, and infection [3,4], and also in cancer, Alzheimer's disease [5], and inflammatory disease [6]. Other studies have suggested an association between the gut microbiome and the development of psoriasis [7], atopic dermatitis [8], hidradenitis suppurativa, acne, and rosacea [9]. Microbiota can also have an impact on ageing.…”
Section: Human Microbiome and Healthmentioning
confidence: 99%